2004
DOI: 10.1016/j.humov.2004.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-motor deficits in children with developmental coordination disorder, attention deficit hyperactivity disorder and autistic disorder

Abstract: Children who have been diagnosed with any one developmental disorder are very likely to meet diagnostic criteria for some other developmental disorder. Although comorbidity has long been acknowledged in childhood disorders, little is understood about the mechanisms that are responsible for the high level of comorbidity. In a series of studies, we have investigated the link between sensory-motor deficits and developmental disorders. Poor sensory-motor integration has long been implicated as a cause of motor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
2
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(162 citation statements)
references
References 60 publications
7
141
2
12
Order By: Relevance
“…In the DSM-IV, the comorbidity between DCD and ADHD is poorly recognized (Piek and Dyck 2004). Poor motor performance in children with ADHD is directly attributed to inattention and hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the DSM-IV, the comorbidity between DCD and ADHD is poorly recognized (Piek and Dyck 2004). Poor motor performance in children with ADHD is directly attributed to inattention and hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, DCD children have been observed to experience difficulties automatizing their gestures: for instance, in contrast with peers, movements to tie shoes continue to require particular attention, even after a great deal of practice. In support of this procedural learning deficit hypothesis, some studies have showed that dysfunction of cerebellum and basal ganglia might be involved in the pathogenesis of DCD (Brookes, Nicolson, & Fawcett, 2007;Cherng, Liang, Chen, & Chen, 2009;Marien, Wackenier, De Surgeloose, De Deyn, & Verhoeven, 2010;Piek & Dyck, 2004;Zwicker, Missiuna, Harris, & Boyd, 2011). For instance, Zwicker et al (2011) explored brain activity during motor procedural learning (trail-tracing task using a joystick) in 7 children with DCD and 7 matched controls.…”
Section: Intact Procedural Motor Sequence Learningmentioning
confidence: 98%
“…In particular, they can have co-morbid reading disabilities and general learning difficulties (Kaplan, Wilson, Dewey & Crawford, 1998;Piek & Dyck, 2004).…”
Section: Working Memory Reading and Mathematical Skills In Children mentioning
confidence: 99%